1
$\begingroup$

If $ a_0 ,a_1 ,\ldots,a_k $ are real numbers such that $$ a_0 + a_1 + \cdots + a_k = 0$$ Find $$ \lim_{n \to \infty } (a_0 \sqrt n + a_1 \sqrt {n + 1} +\cdots + a_k \sqrt {n + k} )$$

I just can't see any solution, can anyone help ?

$\endgroup$
1
$\begingroup$

We have $a_k = -a_0-a_1-\cdots-a_{k-1}$. Hence, $$\sum_{l=0}^k a_l \sqrt{n+l} = \sum_{l=0}^{k-1} a_l\left(\sqrt{n+l} - \sqrt{n+k}\right) = \sum_{l=0}^{k-1}a_l \dfrac{l-k}{\sqrt{n-l}+\sqrt{n-k}}$$ Now you should be able to conclude the answer.

$\endgroup$
  • $\begingroup$ is the limit $0$ ? $\endgroup$ – prebesk Nov 28 '14 at 21:16
  • $\begingroup$ @prebesk Yes${}{}$ $\endgroup$ – Adhvaitha Nov 28 '14 at 21:16
1
$\begingroup$

Since $a_0=-a_1-\cdots -a_k$ we have that

$$\lim_{n \to \infty } (a_0 \sqrt n + a_1 \sqrt {n + 1} + ... + a_k \sqrt {n + k} )=\lim_{n \to \infty } (a_1(\sqrt {n + 1}-\sqrt{n})+\cdots + a_k(\sqrt {n + k}-\sqrt{n}))\\=\lim_{n \to \infty } \left(\frac{a_1}{\sqrt {n + 1}+\sqrt{n}}+\frac{2a_2}{\sqrt {n + 1}+\sqrt{n}}+\cdots + \frac{ka_k}{\sqrt {n + k}+\sqrt{n}}\right)=0,$$

where we have used that $$\sqrt{n+i}-\sqrt{n}=\frac{(\sqrt{n+i}-\sqrt{n})(\sqrt{n+i}+\sqrt{n})}{\sqrt{n+i}+\sqrt{n}}=\frac{i}{\sqrt{n+i}+\sqrt{n}},$$ for $i=1,\cdots, k.$

$\endgroup$
1
$\begingroup$

Using the fact that

$$(1+x)^\alpha \sim_0 1+\alpha x$$ we get

$$a_0 \sqrt n + a_1 \sqrt {n + 1} + ... + a_k \sqrt {n + k}=\sqrt n\left(a_0+a_1\sqrt{1+\frac1n}+\cdots+a_k\sqrt{1+\frac kn}\right)\\\sim_\infty \frac12\sqrt n\left(\frac{a_1+\cdots+a_k}{n}\right)=-\frac{a_0}{2\sqrt n}\xrightarrow{n\to\infty}0$$

$\endgroup$
0
$\begingroup$

Subtract the constrain equation times $\sqrt n$ from the target expression, and you'll see such terms appear:

$$a_i(\sqrt{n+i}-\sqrt n).$$

These can be written as

$$a_i\frac{i}{\sqrt{n+i}+\sqrt n},$$ and obviously then to $0$.

$\endgroup$
0
$\begingroup$

Substitute $n=\frac{1}{p}$. Then: \begin{equation} \lim_{p \to 0} (\frac{a_0}{\sqrt{p}}+\frac{a_1\sqrt{1+p}}{\sqrt{p}}+\ldots+\frac{a_k\sqrt{1+kp}}{\sqrt{p}}) \end{equation}

\begin{equation} \lim_{p \to 0} (\frac{a_0+a_1\sqrt{1+p}+\ldots+a_k\sqrt{1+kp}}{\sqrt{p}}) \end{equation}

This takes $\frac{0}{0}$ form. Thus, apply L'Hospital rule.

Differentiating both numerator and denominator w.r.t $p$

\begin{equation} \lim_{p \to 0} \sqrt{p}(\frac{a_1}{\sqrt{1+p}}+\ldots+\frac{ka_k}{\sqrt{1+kp}}) \end{equation}

which equals $0$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.